Increasing the Quality of Agricultural and Plantation Residues using Combination of Fiber Cracking Technology and Urea for Ruminant Feeds - S. P. Dewi; M. Ridla; E. B. Laconi; A. Jayanegara (Faculty of Animal Science, Bogor Agricultural University, 2018)
This experiment aimed to evaluate the decrease of the fiber fraction of some agricultural and plantation residues after being treated with Fiber Cracking Technology (FCT) and urea. The residues included rice straw, oil palm frond (OPF), oil palm empty fruit bunch (OPEFB), cocoa pod and coffee husk. They were added with 5% urea and incubated in FCT at temperature 135oC and pressure 2.3 atm for 2.5 h. The experimental treatments were arranged as a factorial design 5 × 2, in which the first factor was various agricultural and plantation residues (rice straw, OPF, OPEFB, cocoa pod and coffee husk) and the second factor was FCT application (untreated and treated with FCT + 5% urea), performed in 4 replicates. All treatments were subjected to Van Soest analysis and in vitro digestibility test. The decrease of fiber fraction was confirmed with Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) methods. Results showed that FCT + 5% urea treatment decreased NDF, ADF, cellulose and lignin contents of all samples (P<0.05), and increased IVDMD and IVOMD in comparison to untreated samples (P<0.05). However, the treatment did not alter in vitro methane gas production and VFA profiles of the samples. Analyses using SEM, XRD and FTIR revealed that FCT + 5% urea treatment demolished cell wall component, decreased crystallinity index and cleaved fiber bonds. It was concluded that combination between FCT and urea 5% effectively enhances the quality of some fibrous feed materials.